Limited Ortaklığın Tasfiyesi - Ünlü, Nesibe (Fatih Sultan Mehmet Vakıf Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2021)
Limited ortaklık ülkemizde en çok tercih edilen ortaklık türüdür. Bunun en önemli sebeplerinden biri ise limited ortaklığın kuruluş kolaylığı yanında, sona ermesinin ve tasfiyesinin de kolay olmasıdır. Genel olarak Dünyada ve Türkiye’de son dönemlerdeki ekonomik darboğazlar sebebiyle limited ortaklıkların sona erme ve tasfiye sürecine ilişkin uygulamalar olağan tasfiyelere eklendiğinde sayılar artmıştır. Bilindiği üzere ortaklıkların sona ermesi, sona erme anında tüm ortaklık ilişkilerini de kendiliğinden bitirmez. Hukuken sona ermenin teorik ve pratik sonuçları farklıdır. Sona erme kararı bir süreci başlatır, buna tasfiye süreci denir. Bir tür ortaklıktan önceki duruma veya başa dönmeyi, hukuksal ilişkileri saflaştırmayı ifade eder. İşte bu çalışmada, limited ortaklığın sona ermesi ile birlikte sona ermenin doğal sonucu olan tasfiye süreci, akabinde ise bununla bağlantılı olan ek tasfiye ve tasfiyeden dönme kurumu,6102 Sayılı Türk Ticaret Kanunu hükümleri, doktrin ve yargı kararları ışığında inceleme konusu yapılmıştır.

Limited liability company is the most preferred company type in our country. One of the most important reasons for this is that in addition to the ease of establishment of a limited liability company, it is also easy to terminate and liquidate it. Generally in the world and Turkey, due to recent economic difficulties, termination of limited liability companies and liquidation processes has been increased when ordinary liquidations are considered as well. As it is known, termination of the limited liability company does not automatically cease all partnership relations at the time of termination. Theoretical and practical consequences of legal termination are different. The termination decision commences a process, which is called liquidation. It means a kind of return to the beginning state or state before the establishment of the limited liability company, which refers to the disassociation of legal relations. In our study, liquidation process, which is the natural consequence of termination of the limited liability company, additional liquidation and withdrawal from liquidation processes are examined and analyzed according to relevant provisions of Turkish Commercial Code Numbered 6102, legal doctrine and judicial decisions.
Liquidation of Limited Liability Company
Keywords: Limited Ortaklık; Sona Erme; Tasfiye; Tasfiye Memuru; Ek Tasfiye; Tasfiyeden Dönme; Limited Liability Company; Termination; Liquidation; Liquidator; Additional Liquidation; Withdrawal from Liquidation